"Clear Eyes, Full Hearts, Don't Rape": Subverting Postfeminist Logics on Inside Amy Schumer. Issue 4 (2nd October 2017) - Tully, Meg
ABSTRACT: This study demonstrates the possibilities of perspective by incongruity for feminism, while also noting its limitations, through an analysis of the sketch comedy series Inside Amy Schumer. Series creator Amy Schumer openly identifies as a feminist and utilizes her series to forward feminist politics. As I argue, Inside Amy Schumer 's comedy relies on three incongruous strategies: mimicking patriarchal logics, inverting the grotesque, and juxtaposing serious feminist issues with parodies of frivolous pop culture texts. While flawed, the biting satire of the series pairs with Schumer's offstage activism to debunk the justifying myth of postfeminist culture: that feminism is no longer needed. This study illustrates how irony remains a vital tool for feminist comics even as it recognizes the importance of distinguishing irony from pseudosatire and celebrity feminisms that reproduce dominant ideologies.